Knowledge and Use of HbA1c Among Patients with Type 2 Diabetes Mellitus Admitted in A Tertiary Care Hospital (Journal of Medicine, 2025)
Background: HbA1c test provides an index of average blood glucose level during the past 2-3 months. It is now widely used in management of diabetes both as a measure of long-term glycemic and as a predictor of risk for diabetic complications. In recent years there has been an increased focus on encouraging patients to be aware of HbA1c. Hence, this study was designed to explore the level of knowledge and use of HbA1c test in type 2 diabetic patients in a tertiary hospital.Methods: This cross-sectional descriptive study was conducted among 220 cases of type 2 diabetes mellitus admitted in the medicine ward of Dhaka Medical College and Hospital during the period of May 2024 to November 2024. Each individual was subjected to personal interview regarding demographic details and their level of knowledge of HbA1c by a semi-structured questionnaire. The collected data were analyzed using computer aided statistical software SSPS version 22. Chi2 test and Multivariable Logistic Regression were done to assess the relationship.Results: Among the participants, 59.1% were male and 40.9% were female. Majority (37.3%) were between 41-50 years age group, 26.8% completed higher secondary education and most (71.8%) lived in rural areas. Regarding knowledge of HbA1c test, majority of patients (63.6%) did not know about it. Moreover, only 21.4 % were aware of their target goal. Among aware patients, mean HbA1c was 8.1% whereas among unaware patients who did not know about the test, mean HbA1c was 9.2%. Higher education, urban residence, higher income, and the presence of diabetic complications were significantly associated with greater odds of HbA1c awareness. Patients with graduate-level education had the highest odds (OR = 5.80, 95% CI: 2.50–13.48, p < 0.001). Urban residents (OR = 3.10, 95% CI: 1.76–5.46, p < 0.001) and those with diabetic complications (OR = 2.20, 95% CI: 1.15–4.19, p = 0.017) were also more likely to be aware. Conversely, higher HbA1c levels were associated with lower odds of awareness (OR = 0.75, 95% CI: 0.62–0.91, p = 0.003).Conclusion: Diabetes poses a global health challenge, especially in Bangladesh, where low awareness of HbA1c leads to poor control and complications. This study reveals that most patients lack HbA1c knowledge, resulting in higher levels and more complications. Education and routine testing are crucial to improving diabetes management and outcomes in resource-limited settings. The findings suggest targeted interventions should focus on improving awareness among rural, lower-income, and less-educated populations, as well as patients with poorer glycemic control.J MEDICINE 2025; 26: 20-27